The non-mammalian host Galleria mellonella can be used to study the virulence of the fungal pathogen Candida tropicalis and the efficacy of antifungal drugs during infection by this pathogenic yeast (2013)
ABSTRACT: Although Candida tropicalis is a frequent cause of invasive fungal diseases, its interaction with the host remains poorly studied. Galleria mellonella is a Lepidoptera model which offers a useful tool to study virulence of different microorganisms and drug efficacy. In this work we investigated the virulence of C. tropicalis in G. mellonella at different temperatures and the efficacy of antifungal drugs in this infection model. When larvae were infected with yeast inocula suspensions of different concentrations (4 × 10(6), 2 × 10(6), 10(6) and 5 × 10(5) cells/larva), we observed a dose-dependent effect on the killing of the insect (50% survival ranging from 1.4 ± 0.8 to 8.8 ± 1.2 days with the higher and lower inocula, respectively). Candida tropicalis killed G. mellonella larvae at both 30°C and 37°C, although at 37°C the virulence was more evident. Haemocytes phagocytosed C. tropicalis cells after 2 hours of infection, although the phagocytosis rate was lower when compared with other fungal pathogens, such as Cryptococcus neoformans. Moreover, the haemocyte density in the haemolymph decreased during infection and the yeast formed pseudohyphae in G. mellonella. The efficacy of amphotericin B, caspofungin, fluconazole and voriconazole was tested at different concentrations, and a protective effect was observed with all the drugs at concentrations equivalent to therapeutic dose. Fungal burden increased in infected larvae during time of infection and amphotericin B and fluconazole reduced the number of colony-forming units in the worms. Moreover, antifungal treatment was associated with the presence of cell aggregates around infected areas. We conclude that G. mellonella offers a simple and feasible model to study C. tropicalis virulence and drug efficacy.